2001
DOI: 10.1074/jbc.m006541200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Hydrophobic Binding Site for Anticoagulant Protein S on the β-Chain of Complement Regulator C4b-binding Protein

Abstract: C4b-binding protein (C4BP) is a plasma glycoprotein involved in regulation of the complement system. C4BP consists of seven ␣-chains and one unique ␤-chain, all constructed of repeating complement control protein (CCP) modules. The ␤-chain, made up of three CCPs, binds tightly to vitamin K-dependent protein S, a cofactor to anticoagulant activated protein C. When bound to C4BP, protein S loses its activated protein C cofactor function. In this study, we have mutated potentially important amino acids located at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…The very high affinity of the interaction between protein S and C4BP, its hydrophobic nature, and the very slow rate of dissociation of the complex suggest that the two molecules circulate in blood as a stable complex (2,35,37). In protein S, both LG modules are involved in the binding of C4BP, suggesting that important residues for the interaction are distributed on both modules (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very high affinity of the interaction between protein S and C4BP, its hydrophobic nature, and the very slow rate of dissociation of the complex suggest that the two molecules circulate in blood as a stable complex (2,35,37). In protein S, both LG modules are involved in the binding of C4BP, suggesting that important residues for the interaction are distributed on both modules (37).…”
Section: Discussionmentioning
confidence: 99%
“…The ␣ and ␤ chains are composed of repeating domains of about 60 amino acids denoted complement control protein (CCP) domains. The binding site for protein S is contained in CCP1-CCP2 of the ␤ chain (33)(34)(35). Using a molecular model of the ␤ chain in combination with recombinant ␤ chain expression and site-directed mutagenesis, it has been shown that a solvent-exposed hydrophobic patch in CCP1 lined by a positively charged area on an otherwise negatively charged surface forms the key binding site for protein S (35).…”
mentioning
confidence: 99%
“…The PS binding is totally dependent on the presence of the ␤-chain, the PS binding site being located mainly in the N-terminal CCP (10 -12). The binding site has been further narrowed down by site-directed mutagenesis, highlighting the importance of four amino acids in the N-terminal CCP domain (13).…”
Section: Protein S (Ps)mentioning
confidence: 99%
“…The ␤-chain CCP1 binds protein S, with a hydrophobic patch in CCP1 involving I16, V18, V31, and I33 being particularly important (Figure 4). 17,65 Recently it was found that protein S binds to the negatively charged phospholipid surface that is exposed on apoptotic cells and can mediate phagocytosis of the apoptotic cell. 66,67 In contrast, binding of the protein S-C4BP complex was found to inhibit the phagocytic process.…”
Section: Protein S Affects the Complement System And The Phagocytosismentioning
confidence: 99%